Shuttling happens: soluble flavin mediators of extracellular electron transfer in Shewanella - Brutinel, Evan D.; Gralnick, Jeffrey A. (Applied microbiology and biotechnology, 2012)
The genus Shewanella contains Gram negative γ-proteobacteria capable of reducing a wide range of substrates, including insoluble metals and carbon electrodes. The utilization of insoluble respiratory substrates by bacteria requires a strategy that is quite different from a traditional respiratory strategy because the cell cannot take up the substrate. Electrons generated by cellular metabolism instead must be transported outside the cell, and perhaps beyond, in order to reduce an insoluble substrate. The primary focus of research in model organisms such as Shewanella has been the mechanisms underlying respiration of insoluble substrates. Electrons travel from the menaquinone pool in the cytoplasmic membrane to the surface of the bacterial cell through a series of proteins collectively described as the Mtr pathway. This review will focus on respiratory electron transfer from the surface of the bacterial cell to extracellular substrates. Shewanella sp. secrete redox-active flavin compounds able to transfer electrons between the cell surface and substrate in a cyclic fashion—a process termed electron shuttling. The production and secretion of flavins as well as the mechanisms of cell-mediated reduction will be discussed with emphasis on the experimental evidence for a shuttle-based mechanism. The ability to reduce extracellular substrates has sparked interest in using Shewanella sp. for applications in bioremediation, bioenergy, and synthetic biology.